Cross-Sectional Analyses of Social Determinants of Contraceptive Use among Eligible Couples, Rural Ujjain, Madhya Pradesh - Sharma, Shikha; Mishra, Badri; Sinha, Abhinav (National Journal of Community Medicine, 2017)
Objectives: The present study was conducted to estimate point prevalence of contraceptive use among eligible couples & find out its association with social determinants of eligible couples of rural Ujjain. Methods: Descriptive cross-sectional study conducted from September 2013 to October 2015 on all the eligible couples from 3 selected blocks under Demographic Survey Site of rural field practice area of R.D. Gardi Medical College. Inclusion &exclusion criteria were all consenting eligible couples and couples who were not available at time of interview & sterilized couples. Results: Out of the 263 eligible couples, 136 (52%) couples (male 61% and female 39%) were found to be contraceptive users. Socio-demographic factors significantly associated with current contraceptive use were age (21-25 years) (χ2=8.228, p-value=0.042), sex (males) (χ2=8.925, p-value= 0.003), education (literate) (χ2= 9.226, p-value= 0.026), family planning knowledge (χ2= 5.069, p-value=0.024) and no male child preference (χ2= 7.912, p-value= 0.005). On further regression analysis, sex (p-value= 0.047) and male child preference (p-value= 0.035) were found to be significantly associated. Conclusion: The point prevalence of contraceptive was 52% and determinants of contraceptive use were male gender (O.R. 0.650, C.I. 0.424-0.995) and no male child preference (O.R. 2.074, C.I. 1.054-4.082).